A clinicopathological study of 338 dentigerous cysts. (27th December 2012) - Lin, Hung‐Pin; Wang, Yi‐Ping; Chen, Hsin‐Ming; Cheng, Shih‐Jung; Sun, Andy; Chiang, Chun‐Pin
<x xml:space="preserve">Abstract</x> Background Dentigerous cyst (DC) is one of the most common developmental odontogenic cysts. This hospital‐based retrospective study evaluated the clinical and histopathological features of 338 DCs in Taiwanese patients. Methods In this study, 338 consecutive cases of DCs were collected from January 1995 to December 2009. The demographic data and clinicopathological features of these DC cases were reviewed and analyzed. Results The 338 DCs were taken from 332 patients (212 men and 120 women, mean age 33.0 years, range 5–83 years). There was a significant difference in the mean age between male and female patients (P < 0.05). Of the 338 DCs, 122 were found in the maxilla and 216 in the mandible. The most common site for DCs was the mandibular molar region (169 cases) and the most frequently involved tooth was the mandibular third molar (153 cases). Forty‐six of the 338 DCs were found to be associated with supernumerary teeth. Microscopically, 317 cysts were lined by stratified squamous epithelium, 9 by mucoepidermoid‐typed epithelium, and 12 by ciliated pseudostratified columnar epithelium. Hyaline bodies of Rushton, odontogenic epithelial rests, cholesterol clefts, foamy histiocytes, hemosiderin‐laden macrophages, and dystrophic calcifications were discovered in 11, 78, 90, 33, 62 and 45 DCs, respectively. Conclusion Our results indicate that DCs of Taiwanese patients have a male predominance and occur more frequently in patients between 10 and 29 years of age. The most commonly affected site for DCs is the mandibular molar region and the most frequently involved tooth is the mandibular third molar.